Theories and Practices on Deposit Bonds use for Environmental Management and Sustainable Development in Kenya’s Titanium Mining Projects - Omedo, Geoffrey; Muigua, Kariuki; Mulwa, Richard; Kibugi, Robert (Journal of Sustainable Development Law and Policy, 2025)
This article analyses the use of economic incentives, particularly the Environmental Performance Deposit Bonds (EPDBs) in enhancing sustainable environmentally sound mine operations and closure. This is through a review of the environmental challenges and management practices at the Kwale Mineral Sands ProjecU XIJDI JT ,FOZBlT MBSHFTU NJOJOH project. The article reviews the legal challenges around the effective regulation and application of the bonds for environmental management in upstream mining, as well as how the titanium mining project is undertaking environmental management as the mine approaches its closure deadline in 2023. It is important to note that Base Titanium, the company undertaking this project voluntarily deposited environmental reclamation deposit bonds of USD 512,000 to the environmental regulator, as financial assurance for good environmental practices. The data used in the analysis is from literature review, key informant interviews, interview schedules, and focus group discussions. Results indicate that Base Titanium is working hard to comply to the environmental standards and practices, applying the mitigation hierarchy approaches, as well as a robust mine reclamation process. The lack of a proper legal and regulatory framework governing Environmental Performance Deposit Bonds (EPDBs), as well as a non-existent deposit bonds registry systems and guidelines is a challenge to their effective institutionalization. The public and key stakeholders are also unaware of the existence of the bonds, unlike the well-laid down public participation principles in the Environmental (and Social) Impact Assessments (ESIAs) and Environmental Audits (EAs). While the study acknowledges that Base Titanium is greatly expanding the discourse on sustainable finance models for environmental management in Kenya, the lack of legal clarity and coherence is a major impediment for progressive growth in this area.